PERAN OMBUDSMAN SEBAGAI LEMBAGA PENGAWAS PELAYANAN PUBLIK DI INDONESIA - Br Sebayang, Regina Angelita; Hartati, Hartati (Fakultas Hukum Universitas Jambi, 2021)
This study aims to determine the role of the Ombudsman as an oversight body for the delivery of public services in Indonesia. The Ombudsman of the Republic of Indonesia as an institution that helps the delivery of public services has an important role in the implementation of effective and efficient public services. However, it is realized that they still exist in the implementation of supervision of public services. First, they still represent the Ombudsman of the Republic of Indonesia who cannot be transferred by the invited party because many think that the ombudsman should not be invited. Second, it is constrained by the absence of regulations related to Ombudsman approval and the sanctions that must be applied. Third, there is no punishment execution by the Government for the cancellation of public services to Regional Heads that has been proclaimed by the Indonesian Ombudsman. Both the government and the community must support the implementation of oversight of governance by the Ombudsman in order to create public welfare.